PENGARUH TINGKAT LIKUIDITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANGTERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Tirza Tiara Muhammad; Syamsuri Rahim (Jurnal Akuntansi Aktual, 2015)
This research assessed the financial performance in the short term by using likuidity ratio and profitability ratio. Likuidity ratio illustrates the company’s ability to pay its financial obligations which must be fulfilled immediately, measured by using current ratio. Profitability ratio is used to measure the company’s ability to generate how much profit, measured by using ROA. The company will find way how to maximize the value of its shares which is indicated by its stock price. The stock price which is used in this research is the closing price. This research aims to see how big is the significant influence of likuidity ratio and profitability ratio on the stock price. Sampling technique which is used in this research is purposive sampling.this sampling produced 16 companies. This research uses multiple linear regression analysis. The result showed that independent variables, simultaneously, gave significant positive effect on the dependent variable. Partially, current ratio variable and ROA have positive and significant effect on the closing stock price. Keywords: current ratio, ROA, stock price, closing price